Ecology and management of mangroves - Aksornkoae, Sanit (IUCN, 1993)
This book consists of the following many parts such as the signficance and value of mangroves, environmental factors, mangroves flora, mangrove fauna, mangrove productivity, mangorves degradation and deletion, sivicultural systems for mangroves management, and policy and management.